Postnatal exposure to endosulfan affects uterine development and fertility. (1st July 2020) - Milesi, M.M.; Durando, M.; Lorenz, V.; Gastiazoro, M.P.; Varayoud, J.
Abstract: Endosulfan is an organochlorine pesticide (OCP) used in large-scale agriculture for controlling a variety of insects and mites that attack food and non-food crops. Although endosulfan has been listed in the Stockholm Convention as a persistent organic pollutant to be worldwide banned, it is still in use in some countries. Like other OCPs, endosulfan is bioaccumulative, toxic and persistent in the environment. Human unintentional exposure may occur through air inhalation, dietary, skin contact, as well as, via transplacental route and breast feeding. Due to its lipophilic nature, endosulfan is rapidly absorbed into the gastrointestinal tract and bioaccumulates in the fatty tissues. Similar to other OCPs, endosulfan has been classified as an endocrine disrupting chemical (EDC). Endocrine action of endosulfan on development and reproductive function of males has been extensively discussed; however, endosulfan effects on the female reproductive tract have received less attention. This review provides an overview of: i) the fate and levels of endosulfan in the environment and human population, ii) the potential estrogenic properties of endosulfan in vitro and in vivo, iii ) its effects on uterine development, and iv ) the long-term effects on female fertility and uterine functional differentiation during early gestation. Highlights: Endosulfan exhibits weak estrogenic activity both in vitro and in vivo assays. Neonatal exposure to endosulfan disrupts uterine development with long-term adverse consequences on female fertility. Neonatal exposure to endosulfan induces implantation failures, causing subfertility. Endometrial and myometrial alterations at early pregnancy could account for the endosulfan-induced implantation failures.